Profile of Gamma Glutamyl Transferase (GGT) Levels Among Adolescents with Alcohol Consumption in Pagerbarang District - Jahya, Sulthan; Riyanto, Agus (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Alcoholic Liver Disease is a liver disorder caused by excessive and long-term alcohol consumption. Alcoholic liver disease is divided into fatty liver, alcoholic hepatitis, and cirrhosis. Liver damage can be influenced by many factors such as viruses, bacteria, drug toxicity, chemicals, and excessive consumption of alcoholic beverages. There is a direct relationship between the consumption of hard alcoholic beverages and mortality due to liver cirrhosis. Disruption of mechanisms in the liver can result in swelling with an increase in transaminase enzymes produced by the liver. This research aims to determine Gamma-GT levels in the serum/plasma samples of adolescent alcohol drinkers in Pagerbarang District. Method: This type of research is descriptive research. This method uses total sampling with 30 samples as respondents. Result: The results showed that the 30 research samples had an average respondent age of 15-20 years with a duration of alcohol consumption of 1-3 years. The research results found that all 30 samples had normal Gamma-GT levels. Conclusion: Consuming alcoholic beverages in excessive volume and duration will cause liver damage due to the toxicity of the end products of alcohol metabolism, such as acetaldehyde and hydrogen ions.